The White House Executive Order on the Recovery and Use of Space Resources: Pushing the Boundaries of International Space Law?. (August 2021) - Tronchetti, Fabio; Liu, Hao
Abstract: On April 6, 2020, the White House issued the Executive Order on Encouraging International Support for the Recovery and Use of Space Resources. Due to the controversial matter that it addresses, as well as the unilateral approach that it embraces, unsurprisingly, the Executive Order has spurred a great deal of attention both in the press and academic circles. In light of its significant implications, the purpose of the present paper is to provide a legal and political analysis of the Executive Order and to envision its impact on the future regulation and implementation of space activities. Highlights: The Executive Order challenges traditional space-law making. The Executive Order embraces a bottom-up approach to the formation of space law rules. The Executive Order claims that outer space is not a global common. The Executive Order sets a dangerous precedent for the stability of the space law system. The Executive Order potentially endangers the central law-making role of UNCOPUOS.